Modifying miRs for effective reprogramming of fibroblasts to cardiomyocytes - Xinghua Wang; Syeda S. Baksh; Richard E. Pratt; Victor J. Dzau; Conrad P. Hodgkinson (Elsevier, 2024)
Reprogramming scar fibroblasts into cardiomyocytes has been proposed to reverse the damage associated with myocardial infarction. However, the limited improvement in cardiac function calls for enhanced strategies. We reported enhanced efficacy of our miR reprogramming cocktail miR combo (miR-1, miR-133a, miR-208a, and miR-499) via RNA-sensing receptor stimulation. We hypothesized that we could combine RNA-sensing receptor activation with fibroblast reprogramming by chemically modifying miR combo. To test the hypothesis, miR combo was modified to enhance interaction with the RNA-sensing receptor Rig1 via the addition of a 5'-triphosphate (5'ppp) group. Importantly, when compared with unmodified miR combo, 5'ppp-modified miR combo markedly improved reprogramming efficacy in vitro. Enhanced reprogramming efficacy correlated with a type-I interferon immune response with strong and selective secretion of interferon β (IFNβ). Antibody blocking studies and media replacement experiments indicated that 5'ppp-miR combo utilized IFNβ to enhance fibroblast reprogramming efficacy. In conclusion, miRs can acquire powerful additional roles through chemical modification that potentially increases their clinical applications.